Tourism – economic growth nexus. The case of Romania - Badulescu, Alina; Badulescu, Daniel; Simut, Ramona; Dzitac, Simona (Technological and Economic Development of Economy, 2020)
The development of tourism is usually associated, in positive terms, with economic development, foreign currency inflows, employment opportunities, infrastructure improvements, sustainable development and poverty alleviation. However, the nature of the tourism-growth relationship is still a matter of academic debate, and, perhaps, an expression of the inconsistencies and contradictions of public policies designed to support this industry. Researchers and practitioners have not yet come to an agreement on a number of fundamental questions: does tourism stimulate economic growth or the converse, and whether the causality, if it does exist, is uni or bidirectional, is constant or can change its direction in the medium - or long run. The present paper investigates the relationship between Gross Domestic Product (GDP) per capita and international tourism in Romania, over the 1995–2016 period. Our results show that the causal effect of the GDP on the international tourist arrivals and on the international tourism receipts is significant in the long run in Romania. In the short-run, we find a unidirectional causal relationship from the international tourism receipts to GDP, and a bidirectional causal relationship between GDP and the number of international tourist arrivals.First published online 8 May 2020